2022
DOI: 10.7860/jcdr/2022/53257.15951
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Cuff Closure by Endosuturing in Total Laparoscopic Hysterectomy as Compared to Transvaginal Route of Suturing

Abstract: Introduction: In present times, Total Laparoscopic Hysterectomy (TLH) is one of the commonly performed gynaecological procedure. Vaginal vault or cuff closure is crucial and critical in performance of TLH. During TLH, vaginal vault or cuff closure is done using a variety of available sutures. The techniques of suturing and approaches, either endoscopic or transvaginal, can vary. The skill, experience and preference of the surgeon counts in the final outcome of the surgery. Aim: To compare and study the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study done by Kanupriya Singh found that in the laparoscopic technique; sutures are inverted and not subjected to vaginal bacteria; thus, there is a lesser possibility of postoperative vault infection and less possibility of vault dehiscence. [ 13 ] In a study done in India, 600 patients underwent hysterectomies, both laparoscopic and abdominal route. It was observed none of them had postoperative vault infection.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Kanupriya Singh found that in the laparoscopic technique; sutures are inverted and not subjected to vaginal bacteria; thus, there is a lesser possibility of postoperative vault infection and less possibility of vault dehiscence. [ 13 ] In a study done in India, 600 patients underwent hysterectomies, both laparoscopic and abdominal route. It was observed none of them had postoperative vault infection.…”
Section: Discussionmentioning
confidence: 99%